Profitabilitas dan Manfaat Ekonomi bagi Anggota di Koperasi Konsumen Mitra Usaha Cisempur - Iwan Mulyana; Linda Rismayanti; Tryiis ARR (J-Coop : Journal of Co-operative, 2025)
This study aims to analyze the profitability (rentability) and its relationship with the economic benefits received by members of the Mitra Usaha Cisempur Consumer Cooperative in Jatinangor District, Sumedang Regency. Profitability, measured through Return on Assets (ROA) and Return on Equity (ROE), reflects the cooperative’s efficiency in managing its assets and equity to generate residual income (SHU). The study uses a quantitative descriptive approach, with financial report data from 2019 to 2023 serving as the basis for analysis. Results show fluctuating profitability levels over the five-year period, with a declining trend in both ROA and ROE, which indicates inefficiencies in asset and equity management. Furthermore, the economic benefits received by members, both direct and indirect, were significantly impacted by the cooperative’s declining profitability. The findings highlight the need for improved operational efficiency and strategic financial management to optimize benefits for cooperative members.